The Jurimetri Formulation of Court Decisions in the Division of Joint Property - Khoirunnisa, Khoirunnisa; Hidayati, Rahmi (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
This paper analyzes the results of court decisions on the application of jurimetric formulations in the division of joint property as an effort of justice. Jurimetry can be used as an option when the division of joint property regulated in the Compilation of Islamic Law does not guarantee justice to the parties. Jurimetry emphasizes the division of joint property based on the implementation of the obligations and responsibilities of each party while bound by marriage, so that the use of jurimetry will provide a greater sense of justice. The focus of this article is how the jurimetry formulation of court decisions in cases of division of joint property and its relevance to the principles of justice. This article is a literature research with a normative approach. The source of data in writing this article is court decisions regarding joint property. The result is that the application of jurimetry in the division of joint property can provide more justice for the parties. Parties who do not carry out their obligations in full will have their rights to joint property reduced in accordance with their actions. Conversely, parties who carry out their obligations in full will get rights in accordance with their actions. If both parties carry out their obligations in full, then both are entitled to the same amount of joint property. The recommendation of the results of this writing is that the judge can use this jurimetric formulation as a consideration in handling joint property disputes. Keyword: Jurimetry, Joint Property, Justice and Legal Reform